2014
DOI: 10.3390/molecules191221411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Platycodin D on Proliferation, Apoptosis and PI3K/Akt Signal Pathway of Human Glioma U251 Cells

Abstract: Effects of platycodin D (PD) on the proliferation, apoptosis and PI3K/Akt signaling pathway of human glioma U251 cells were investigated. Glioma U251 cells were treated with PD at final concentrations of 0, 16.3, 40.8, 81.6, 163.2 μM, and inhibition rate, early and late apoptotic rate, apoptotic index, expression of apoptosis-related proteins and phosphorylation of the PI3K/Akt signaling pathway were evaluated. The results showed that compared with the control group, PD could increase the proliferation inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…High grade glioma is the leading cause of brain cancer-related mortality due to its high invasive ability and malignant proliferation (1,2). Glioma incidence accounts for approximately 40-50% of all intracranial tumors (3). Although current treatment has modestly improved patient survival, patients with gliomas still have a very poor prognosis and low cure rates.…”
Section: Introductionmentioning
confidence: 99%
“…High grade glioma is the leading cause of brain cancer-related mortality due to its high invasive ability and malignant proliferation (1,2). Glioma incidence accounts for approximately 40-50% of all intracranial tumors (3). Although current treatment has modestly improved patient survival, patients with gliomas still have a very poor prognosis and low cure rates.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we provided evidence that platycodin D had the ability to cause growth suppression and apoptosis in OSCC cells. The antiproliferative activity of platycodin D has also been observed in other malignancies such as breast cancer, glioma, and prostate cancer . It has been reported that platycodin D promotes caspase‐mediated apoptosis in AGS human gastric cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…PGD is classified as a triterpenoid saponin and is one of the main chemical components of P. grandiflorum. PGD has a very similar structure to Platycodin D, a well known anticancer agent (11)(12)(13)(14). Based on this relationship, we hypothesized that PGD would also have anticancer effects.…”
Section: Introductionmentioning
confidence: 99%